Analysis of Ethnic Group Relations in Living Life - Christianto, Rafael Grady; Febisahfitri, Rieanda; H, Erdi Husnul; F, Rahmadita Anisa; Hutapea, Bonar (Universitas Muhammadiyah Metro, 2017)
This research uses qualitative method approach. The data is taken through semi structured interviews so that the researcher can get the deepest information from the subject but still use interview and observation guidance. Aims to determine the perspectives between ethnic groups by looking at how the interactions or relationships that occur in everyday activities, the management of conflicts, what activities are usually done together, and the attachment that exists between various ethnic groups in Kelurahan Pengasinan Kota Bekasi to meet Practical needs. The theory used is the group definition theory of Joseph S. Roucek, Major Polak, and Wila Huky, inter-group relations of Kinloch and Stanley Liberson, social interaction theory of Soekanto, Sunarto-majority minority relations theory, Budiman, Suparlan and Edward M Bruner, and the inter-ethnic perspective theory of Setiaman. Social relations itself has a sense of relationship in which there are interactions that occur in society in order to prevent the emergence of conflict. Based on the results of research and discussion that has been done, it can be concluded that, good interaction among ethnic groups is the key in maintaining relationships among ethnic groups. This will affect the survival, social behavior, and perspectives that arise and develop among others.